Government debt, inflation dynamics and the transmission of fiscal policy shocks - Eric Mayer; Sebastian Rüth; Johann Scharler (University of Würzburg, Department of Economics, 2012)
We analyze the influence of the fiscal position on the transmission of government spending shocks in a New Keynesian model. We find that once we allow for positive levels of government debt in the steady state, the sign and the size of the fiscal multiplier depend strongly on the horizon at which the multiplier is evaluated. While the long-run effect of a fiscal policy innovation is typically of a similar order of magnitude as in Gali et al. (2007), short-run multipliers differ substantially. The reason for this non-monotonic behavior is the interaction between the dynamics of the inflation rate and the debt level in real terms, which is absent in standard models in which government debt is restricted to be equal to zero in the steady state.
Keywords: E31; E62; H63; 330; fiscal multiplier; New Keynesian model; government debt; inflation; Finanzpolitik; Multiplikator; Neukeynesianische Makroökonomik; Öffentliche Schulden; Inflationsrate; Dynamisches Modell; Theorie